The U2B'' RNP motif as a site of protein-protein interaction. - Scherly, D (1990)
The U2 snRNP contains two specific proteins, U2B'' and U2A'. Neither of these proteins, on its own, is capable of specific interactions with U2 RNA. Here, a complex between U2B'' and U2A' that forms in the absence of RNA is identified. Analysis of mutant forms of U2B'' shows that the smallest fragment able to bind specifically U2 RNA (amino acids 1-88) is also the minimal region required for complex formation with U2A', and implies that this region must be largely structurally intact for U2A' interaction. Although this truncated U2B'' fragment is capable of making specific protein--RNA and protein-protein interactions its structure, as measured by the ability to bind to U2A'', appears to depend on the rest of the protein. Hybrids between U2B'' and the closely related U1A protein are used to localize U2B'' specific amino acids involved in protein-protein interaction. These can be divided into two functional groups. U2A' interaction with U2B'' amino acids 37-46 permits binding to U2 RNA whereas interaction with U2B'' specific amino acids between positions 14 and 25 reduces non-specific binding to U1 RNA. These two proteins may serve as a general example of how RNA binding may be modulated by protein-protein interaction in the assembly of RNPs, particularly since the region of U2'' involved in interaction with U2A' consists mainly of a conserved RNP motif.